Определение расхода топливного газа в газоперекачивающем агрегате с газотурбинным приводом и центробежным нагнетателем - Олейник, Юрий Анатольевич; Сапрыкин, Сергей Алексеевич; Науменко, Светлана Петровна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Разработан алгоритм расчета расхода топливного газа на газоперекачивающем агрегате (ГПА) с газотурбинным приводом (ГТП) и центробежным нагнетателем (ЦБН). В алгоритме учитываются ограничения параметров ГПА: минимальный расход газа в ЦБН, минимальная мощность ГТП, максимальная температура и степень сжатия газа в ЦБН. Дополнительно разработан алгоритм определения числа рабочих ГПА при задании общего расхода перекачиваемого газа для n однотипных ГПА.

An algorithm for calculating the flow rate of fuel natural gas in a gas pumping unit (GPU) (GPU drive) and for several identical gas pumping units operating together in compressor shop or compressor station. The flow calculation model takes into account thermal characteristics, operating modes and limitations of GPU parameters. Main task when determining consumption fuel gas is the calculation of the capacity of compressor shops and GPU. Power calculation takes into account compression ratio and flow rate of gas pumped by compressors. After calculation of GPA working capacity GPA drives efficiency factor is determined and fuel gas flow rate in GPU (GPU drive) is calculated. Exact values and limitations of thermal parameters (allowable pressures, temperatures, pumped gas flow rates, efficiency factors of compressors and drives). At the same time, the parameters of the GPU will depend on its operating mode of the GAP. The algorithm takes into account four limitations of GPU parameters: minimum flow rate of pumped gas in GPU compressor, minimum drive power of the GPU compressor, maximum gas temperature at the outlet of the GPA compressor, maximum gas compression ratio in the compressor. Without taking into account these restrictions, the calculation of fuel gas may be incorrect, since the impossible operation mode of the GPU will be taken into account. Developed algorithm takes into account all necessary characteristics and limitations of GPU parameters, simulates real robot modes of existing and designed GPU.
Determination of fuel gas flow rate in gas pumping unit with gas turbine drive and centrifugal supercharger
Keywords: компрессор; привод; центробежный нагнетатель; compressor; drive; centrifugal supercharger